Lack Of Basic Education Accessibility In The Periphery Area Of Indonesia (A Research in Takirin Village, Tasifeto Timur Sub-District, Belu Regency, NTT Province - Indonesia) - M. N. B. C. Neolaka; Rikhardus S. Klau; Metriani Epifania Nahak (Iapa Proceedings Conference, 2018)
The presence of a school in the village is a sign of the concrete presence of the State to fulfill the basic rights of the community in the field of education. Remembering that schools always assume interaction with other elements of society such as parents, students, religious institutions and village governments, their presence also demands responsibility and involvement of all parties at the grassroots in synergic cooperation. Only through quality cooperation involving all parties, an educational institution can become the backbone of a society's progress. Quality cooperation can be evaluated by looking at how the community responds to the concrete problems they face in the field. One of the fundamental problems commonly found in remote areas of Indonesia is the low access to basic education services. By recognizing and identifying problems that occur in their own environment, people are encouraged to recognize violations of their basic rights. In turn, the people themselves are encouraged to collect their rights to the Government and at the same time are aware of being actively involved in development.